FOREIGN EXPERIENCE IN DEVELOPING HUMAN CAPITAL AND FINANCIAL LITERACY AND ITS POTENTIAL USE IN UZBEKISTAN - Tuychiyeva Xayotxon Gapurjonovna (European Science Publishing, 2025)
This article explores foreign experience in developing human capital and financial literacy, focusing on successful international practices and their applicability to Uzbekistan. It analyzes key strategies implemented globally to enhance workforce skills and improve public understanding of financial matters. The article considers the socio-economic context of Uzbekistan and discusses how these foreign approaches could be adapted to promote sustainable economic growth and social well-being through improved education and financial awareness.
Keywords: Human capital, financial literacy, foreign experience, education, economic development, Uzbekistan, workforce skills, financial education.